2015
DOI: 10.3177/jnsv.61.391
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Amounts of Calcium Intake on Bone Mass and Arterial Calcification in Ovariectomized Rats

Abstract: SummaryReduced estrogen secretion and low calcium (Ca) intake are risk factors for bone loss and arterial calcification in female rodents. To evaluate the effects of Ca intake at different amounts on bone mass changes and arterial calcification, 8-wk-old female Wistar rats were randomly placed in ovariectomized (OVX) control and OVX with vitamin D3 plus nicotine (VDN) treatment groups. The OVX with VDN rats were then divided into six groups to receive different amounts of Ca in their diets: 0.01%, 0.1%, 0.3%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
(53 reference statements)
2
5
1
Order By: Relevance
“…The reduction in Ca that was used in the work of Viguet-Carrin et al [ 21 ] represented a decrease in the Ca content of the diet of around 60%; however, no data on specific Ca intake were provided by the authors. There are a handful of studies that show a similar level of Ca restriction compared to our study, for example, Agata et al [ 22 ]. Agata et al [ 22 ] showed that a Ca intake of below 0.3% (representing a 50% decrease in comparison to the control) resulted in a significant reduction in BMD of the tibia.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The reduction in Ca that was used in the work of Viguet-Carrin et al [ 21 ] represented a decrease in the Ca content of the diet of around 60%; however, no data on specific Ca intake were provided by the authors. There are a handful of studies that show a similar level of Ca restriction compared to our study, for example, Agata et al [ 22 ]. Agata et al [ 22 ] showed that a Ca intake of below 0.3% (representing a 50% decrease in comparison to the control) resulted in a significant reduction in BMD of the tibia.…”
Section: Discussionsupporting
confidence: 80%
“…There are a handful of studies that show a similar level of Ca restriction compared to our study, for example, Agata et al [ 22 ]. Agata et al [ 22 ] showed that a Ca intake of below 0.3% (representing a 50% decrease in comparison to the control) resulted in a significant reduction in BMD of the tibia. Our study is unique in the context of the literature due to a restriction of P intake, which did not occur in any of the above studies [ 1 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 80%
“…The main index for evaluating the effect of treatments on postmenopausal osteoporosis (POP) is the increase in BMD. Estrogen deficiency, in both OVX rats and in postmenopausal women, can lead to a reduction in BMD ( 14 , 15 ). In the present study, treatment with ICA significantly improved BMD and effectively prevented the loss of bone mass caused by the OVX-induced lack of estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in both the assays used, for example, animal models, cell culture systems, and human trials, and the milk components (whole milk or a fraction of milk) investigated, can lead to variable outcomes in the assessment of the effect of milk on bone health. For example, a range of metrics such as break force, mineral composition, and microstructure can be used to assess the effects of samples on bone density or bone fracture risk (Agata et al., ; Weaver et al., ), resulting in different outcomes. Confounding factors such as the milk fraction used, heat treatment, and enzymatic and microbial effects during milk processing can result in subtle changes in variables such as mineral solubility, protein functionality, and lipid oxidation (El Zubeir, Basher, Alameen, Mohammed, & Shuiep, ; Ibrahem & El Zubeir, ).…”
Section: Introductionmentioning
confidence: 99%